Dynamic responses of wearable thermoelectric generators used for skin waste heat harvesting. (1st January 2023) - Zhang, Aibing; Pang, Dandan; Wang, Baolin; Wang, Ji
Abstract: A thermodynamic model for skin and wearable thermoelectric generators (WTEGs) system is developed based on dual-phase-lag (DPL) bioheat transfer. Human skin is regarded as a multi-layer structure consisted of subcutis, dermis and epidermis. Analytical solutions for temperature profile inside skin-WTEG system and energy conversion performance of WTEGs are obtained. Numerical results show that very small deviations for power output of WTEGs are caused by using the room-temperature physical properties of Bi2 Te3 -based thermoelectric semiconductors. However, the effect of heat convection by blood perfusion inside skin tissue should be considered to estimate energy conversion performance of WTEGs accurately. The influence of the contact thermal resistance between the skin and WTEG can be neglected when the thermal conductance ratio of the skin-WTEG interface to the flexible substrate is larger than 0.1. It takes more than 10 min to attain the steady-state again when a thermal perturbation is applied to the skin-WTEG system. The classic Fourier bioheat transfer model may also provide acceptable accuracy for the energy conversion analysis of WTEG compared with the non-Fourier bioheat transfer model if the response time exceeds 1 min. This paper provides a useful theoretical model for designing WTEG devices. Highlights: The physiological characters of human skin are taken into account. Contact thermal resistance between skin and WTEG should be considered. It takes more than 10 min to attain steady-state after a thermal perturbation. Non-Fourier effect of skin can be neglected if the response time exceeds 1 min. An iterative solution technique is presented to estimate dynamic response of WTEG.